Can increasing infestations by Rhynchophorus ferrugineus threaten endemic Chamaerops humilis in Sardinia (Italy)?. (29th June 2019) - Cocco, A.; Pusceddu, M.; Lentini, A.; Floris, I.
Abstract : The red palm weevil, Rhynchophorus ferrugineus, is the most devastating pest of the Canary palm, Phoenix canariensis, in the Mediterranean Basin. Sporadic infestations have also been observed in other cultivated palm species and, above all, in the endemic European fan palm, Chamaerops humilis . Considering the high ecological importance of C. humilis in coastal ecosystems, the present paper gives an update on the status of R. ferrugineus infestations on the European fan palm in Sardinia (Italy). Since the introduction of R. ferrugineus into Sardinia, attacks of this pest on C. humilis have been limited but have increased in the last 2 years, including infestations on eight naturally growing palms in a Natura 2000 site. Male and female red palm weevils that emerged from C. humilis were similar in size to those of P. canariensis, indicating that the quality of these two feeding substrates is similar. The limited number of infested European fan palms observed so far suggests caution when predicting a rapid spread of this pest in cultivated and non‐cultivated C. humilis palms. Nonetheless, natural populations of C. humilis along western Mediterranean shores should be monitored in order to highlight the potential establishment of R. ferrugineus in these habitats. L'augmentation des infestations par Rhynchophorus ferrugineus peut‐elle menacer l'espèce endémique Chamaerops humilis en Sardaigne (Italie) ?: Le charançon rouge du palmier, Rhynchophorus ferrugineus, est l'organisme nuisible le plus dévastateur du palmier des Canaries, Phoenix canariensis, dans le bassin méditerranéen. Des infestations sporadiques ont également été observées sur d'autres espèces de palmiers cultivés, surtout sur le palmier nain Européen Chamaerops humilis. Compte tenu de la grande importance écologique de C. humilis dans les écosystèmes côtiers, cet article fait le point sur l'état des infestations par R. ferrugineus sur le palmier nain Européen en Sardaigne (Italie). Depuis l'introduction de R. ferrugineus en Sardaigne, les attaques de cet organisme nuisible sur C. humilis ont été limitées, mais ont augmenté au cours des deux dernières années. Notamment, huit de ces palmiers poussant en milieu sauvage ont été retrouvés infestés sur un site Natura 2000. Les mâles et les femelles du charançon rouge du palmier qui ont émergé de C. humilis étaient de taille similaire à ceux émergeant de P. canariensis, ce qui indique que la qualité alimentaire de ces deux substrats est similaire. Le nombre limité de palmiers nains Européens infestés qui ont été observés jusqu'à présent incite à être prudent avant d'évoquer une dissémination rapide de cet organisme nuisible sur les palmiers C. humilis cultivés et non cultivés. Néanmoins, les populations naturelles de C. humilis le long des rives ouest de la Méditerranée devraient être suivies afin de mettre en évidence l'établissement potentiel de R. ferrugineus dans ces habitats. Может ли растущая заражённость долгоносиком Rhynchophorus ferrugineus угрожать эндемичным Chamaerops humilis на Сардинии (Италия)?: Красный долгоносик, Rhynchophorus ferrugineus, является самым губительным вредителем канарской пальмы, Phoenix сanariensis, в Средиземноморском бассейне. Спорадические заражения наблюдались также на других культивируемых видах пальм и, прежде всего, на эндемичной европейской веерной пальме Chamaerops humilis . Учитывая высокую экологическую значимость C. humilis для прибрежных экосистем, в настоящей работе приводится обновленная информация о состоянии заражённости европейской веерной пальмы на Сардинии (Италия) R. ferrugineus . С момента интродукции R. ferrugineus на Сардинии атаки этого вредителя на C. humilis были ограничены, однако они участились в последние два года, включая заражение восьми естественно растущих пальм на территории парка "Natura 2000". Самцы и самки красного пальмового долгоносика, отродившиеся из C. humilis, имели размеры, аналогичные размерам P. canariensis, что указывает на качественное сходство этих двух питательных субстратов. Ограниченное количество зараженных европейских веерных пальм, наблюдаемое до сих пор, склоняет к осторожности при прогнозировании быстрого распространения этого вредного организма на культивируемых и некультивируемых пальмах C. humilis . Тем не менее, естественные популяции C. humilis вдоль западного побережья Средиземноморья нуждаются в мониторинге, чтобы придавать большое значение потенциальной акклиматизации R. ferrugineus в этих местах обитания.